2021
DOI: 10.5812/ijp.105094
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Level of Interleukin-33 and Allergic Rhinitis and Its Severity in Children

Abstract: Background: T helper type 2 (Th2) cells are critical cellular elements in allergic rhinitis. Interleukin-33 (IL-33) produces Th2-related cytokines and binds to the ST2 receptors. This is expressed strongly in mastocytes and discerningly in Th2 cells. Through Th2 cells, IL-33 may also have partly involved in immune responses. Objectives: This study aimed to measure the IL-33 serum levels in children suffering from allergic rhinitis and investigate its relationship with the disease. Methods: This case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Males comprised the majority of patients in a retrospective cross-sectional study with nasal polyps; their mean age was 39.49±16.63 years [24] . Heidarzadeh Arani et al [25] demonstrated that 18 (31.6 %) of the 57 patients with AR were females, while 39 (68.4 %) were males.…”
Section: Discussionmentioning
confidence: 99%
“…Males comprised the majority of patients in a retrospective cross-sectional study with nasal polyps; their mean age was 39.49±16.63 years [24] . Heidarzadeh Arani et al [25] demonstrated that 18 (31.6 %) of the 57 patients with AR were females, while 39 (68.4 %) were males.…”
Section: Discussionmentioning
confidence: 99%